Determinan Kepatuhan Wajib Pajak UMKM Dengan Modernisasi Sistem Administrasi Perpajakan Sebagai Variabel Moderasi - Ari Pratama; Dekar Urumsah (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to analyze and test the influence of tax understanding, tax policy and tax sanctions on taxpayer compliance in UMKM with modernization of the tax administration system as a moderating variable. Methodology/approach: Associative research using a quantitative approach. This study uses survey methods and questionnaire techniques which are distributed directly or online to UMKM actors. The total data that met to be analyzed amounted to 123 and were analyzed using the Smart Partial Least Square. Findings: The results of the research state that tax policy and tax sanctions influence taxpayer compliance in UMKM. Practical implications: This research is important because it can provide input to the Directorate General of Taxes regarding UMKM taxpayers. Originality/value: Adding the tax administration system modernization variable as a moderating variable to determine the factors that mediate behavioral intentions with actual behavior.